2011
DOI: 10.1515/bmt.2011.022
|View full text |Cite
|
Sign up to set email alerts
|

Electric impedance tomography for monitoring volume and size of the urinary bladder

Abstract: A novel non-invasive technique for monitoring fluid content in the human bladder is described. Specifically, a precommercial electric impedance tomograph (EIT) was applied to measure and visualize impedance changes in the lower torso due to changes in bladder volume. Preliminary measurements were conducted during routine urodynamic tests of nine male paraplegic patients, in whom a contrast agent was slowly infused into the bladder for diagnostic purposes. In some patients, a good correlation between bladder vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 23 publications
1
42
0
Order By: Relevance
“…To the knowledge of the authors, the first application of EIT for cystovolumetry has been reported by our group in 2011 [7]. In this study, nine male paraplegic patients have been monitored by EIT during regular urodynamic examination.…”
Section: Eit For Cystovolumetrymentioning
confidence: 96%
See 2 more Smart Citations
“…To the knowledge of the authors, the first application of EIT for cystovolumetry has been reported by our group in 2011 [7]. In this study, nine male paraplegic patients have been monitored by EIT during regular urodynamic examination.…”
Section: Eit For Cystovolumetrymentioning
confidence: 96%
“…For EIT measurement, the set-up has been kept close to the human experiment performed in 2007 [7] incorporating an EEK1 (Dräger Medical, Lübeck, Germany) EIT device with adjacent injection and measurement pattern as well as an elastic belt with 16 conductive rubber electrodes. Solutions of demineralized water with sodium chloride concentrations of 0%, 0.9% and 1.8% accoding to conductivities of ∼0 mS/cm, ∼15 mS/cm and ∼28 mS/cm have been prepared.…”
Section: Impact Of Urine Conductivity On Impedance Cystovolumetrymentioning
confidence: 99%
See 1 more Smart Citation
“…Methods of measuring the electrical properties of tissue at both low and high frequencies can be used to monitor the bladder volume and aid in providing clinical feedback to the clinician that can enhance decision-making with urinary incontinence [8]. To determine the bladder volume, the data can be associated with the bladder volume by metrics [9], [10] or by machine learning [10].…”
Section: Introductionmentioning
confidence: 99%
“…However, the performance of the NN was found to deteriorate when pushed outside training boundaries, such as in the extrapolating of unseen bladder volumes [10]. Bladder volume has been shown to have a 'near' linear trend with electrical properties [8]. Thus, a better machine learning algorithm may be linear regression for extrapolating bladder volume.…”
Section: Introductionmentioning
confidence: 99%